THE REFLECTION OF THE SOCIO-ECONOMIC LIFE OF THE SOGDIANS IN THE SOURCES IN THE SOGDIAN LANGUAGE - Sattorov Eldor Bobir o‘g‘li (Zeta Repository, 2023)
Information about the socio-economic life of the Sogdians is recorded in a number of sources. One of them is the sources in the Sogdian language, the importance of which is considered high in the study of their socio-economic life. In this article, the documents in the Sogdian language, which reflect the social life of the people of early medieval Sogdian, have been studied.